Korelasi Persebaran Bahasa Austronesia dengan Persebaran Temuan Artefak Gerabah di Papua - Hari Suroto (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Based on the language mapping in Papua have mentioned that the Austronesian languages and non-Austronesian. Based on the mapping of the language is known in Pegunungan Tengah and inland areas can not find the Austronesian language of Papua, while the non-Austronesian languages are found only in inland and coastal. Austronesian languages found along the northern coast of Papua, coastal and island in Teluk Cenderawasih, and the coast of Kepala Burung. Austronesia languages in Papua brought by Austronesian speakers who migrated to this area in 1500 until 1000 BC. Based on this record so that there are areas of Papua Austronesia language that is expected to have pottery material culture.